2021
DOI: 10.1158/2159-8290.cd-21-0219
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Response and Intrinsic Resistance to PD-1 Blockade in Microsatellite Instability–High Gastric Cancer

Abstract: Sequence alterations in microsatellites and an elevated mutational burden are observed in 20% of gastric cancers (GC) and associated with clinical response to anti-programmed death (PD)-1 antibodies. However, 50% of microsatellite instability-high (MSI-H) cancers are intrinsically resistant to PD-1 therapies. We conducted a phase II trial of pembrolizumab in advanced MSI-H GC patients and included serial and multi-region tissue samples in addition to serial peripheral blood analyses. The number of whole-exome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 79 publications
8
106
0
Order By: Relevance
“…Though MSI-H, dMMR or TMB-high molecular phenotype varies among cancer patients, and not all patients with the MSI-H, dMMR or TMB-high phenotype respond to the ICIs therapy. In this context, exploration of mechanisms underlying resistance to ICIs is necessary (44,45). Moreover, due to many challenges, such as high variation in inter-assay precision and cut-off values associated with routine immunohistochemistry, multicolor flow cytometry can serve as a reliable and efficient alternative method.…”
Section: Discussionmentioning
confidence: 99%
“…Though MSI-H, dMMR or TMB-high molecular phenotype varies among cancer patients, and not all patients with the MSI-H, dMMR or TMB-high phenotype respond to the ICIs therapy. In this context, exploration of mechanisms underlying resistance to ICIs is necessary (44,45). Moreover, due to many challenges, such as high variation in inter-assay precision and cut-off values associated with routine immunohistochemistry, multicolor flow cytometry can serve as a reliable and efficient alternative method.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in patients with NSCLC who were pretreated with nivolumab, PD-1 + CD8 T cells at baseline were more frequently detected in patients with clinical benefit (CB) than in those with non-response (NR) [27]. Furthermore, a recent study showed that a higher percentage of circulating PD-1 + CD8 T cells at baseline was associated with a clinical benefit in patients with MSI-high gastric cancer treated with pembrolizumab [28].…”
Section: Pd-1 or Pd-l1 Expressing Cd8 T Cellsmentioning
confidence: 99%
“…In a more recent study, Transcription Factor 7 (TCF7)-but not PDCD1 (PD-1 gene)-expression, was found to be a positive predictor of tumor regression in melanoma [63]. In MSI-high gastric cancer, a diverse T cell receptor (TCR) repertoire and the presence of early-to-intermediate activation status T cells in tumor tissues were found to be associated with an ICT response [68]. As T cell activation and exhaustion are confounding processes, exhaustion markers are good indicators of the presence of tumor-directed immunity; however, terminal differentiation of collective tumor-specific T cells in the exhausted state may adversely influence the ICT response.…”
Section: Gastric Cancer Tumor Scrna-seq Pd-1+ Cd8+ T Cellmentioning
confidence: 99%
“…The abundance of PD-1+ CD8+ T cells correlate with response and longer survival to PD-1 blockade. [68] Comparison between responders and non-responders provides critical information regarding patient stratification and the mechanism of action of ICT [69]. Characterization of post-treatment samples helps define the immune cell dynamics and state transitions [70].…”
Section: Gastric Cancer Tumor Scrna-seq Pd-1+ Cd8+ T Cellmentioning
confidence: 99%
See 1 more Smart Citation